Evaluation of respondents' attitude towards mandatory and private pension insurance - Živković Milica; Piljan Ivan; Piljan Tatjana (Trendovi u Poslovanju)
In most countries and especially in 'countries in transition', the pension insurance systems are in crisis and they are trying to establish a model of sustainable functionality through reforms. In the period from 2001 to 2014, Serbia was reforming the pension system in order to deal with all the problems like: high deficit, debt, employees - pensioners ratio, negative demography, etc. In this paper, we have shown the research results in order to evaluate the opinions of the citizens of Niš about the existent compulsory pension insurance and the trust in private insurance, as well as to hear opinions on the need for the additional reforms of the system. The Hypo thesis Ho has been proven true: The citizens are not satisfied with the existent state of the retirement insurance, they think that the pension fund is empty and that it cannot guaranty reliable pensions. That means that reforms, taken until now, were not enough and that they need to be continued.